Student autonomy as the goal of education and education - Munćan, Suzana (Norma, 2023)
The paper discusses student autonomy as part of the education in the context of school modernization. The very concept autonomous for a student does not have a single definition. Proponents of student autonomy in their theoretical statements emphasize how important its development is for a person in the XXI century. In a brief consideration of the educational goals of certain advanced educational systems, it was observed that school to a certain extent support autonomy of a student, which varies among different educational institutions the systemhas. In the education system of the Republic of Serbiathe focus of the goal of upbringing and education is on the acquisition of knowledge and skills, and far less on the student’s personality and their individual development. Level of student autonomy is emphasized to a greater extent within elective subjects, extracurricular activities (sections) and extracurricular activities. The work points out that question of appreciation of the student’s personality, development of his potential and promoting of autonomy in the school context should be solved through the goal of education and upbringing, that is, that the aim of upbringing and education which respects the autonomy of students is necessary for the school of the modern age.